Ancient Egypt a fact-filled coloring book - Manuelian, Peter Der 1959-; Driggs, Helen I. (Running Pr., 1997)
In this fact-filled coloring book learn about Egyptian rulers, the Nile River, mummies, monuments and architectural wonders, hieroglyphs, The Rosetta Stone, food, fashion, education, and other aspects of daily life 5,000 years ago.
Keywords: Funde; Art, Egyptian; Art, Egyptian -- Juvenile literature; Coloring books; Egypt -- Antiquities -- Juvenile literature; Egypt -- Civilization -- To 332 B.C; Egypt -- Civilization -- To 332 B.C. -- Juvenile literature